Parabens and estrogen-mediated cancers: unraveling coincidence, co-occurrence, and causality - Zehra Esra Ilhan; Andrea Marchetto; Georgia Lorentzen; Paweł Łaniewski; Leslie V. Farland; Melissa M. Herbst-Kralovetz (npj Women's Health, 2026)
Abstract Paraben esters are endocrine disruptors linked to breast cancer, yet their role in other estrogen-mediated cancers remains limited. Preclinical evidence suggests that parabens accumulate in tissues and may promote carcinogenesis, while clinical data indicate widespread exposure. Our re-analysis of cervicovaginal metabolomes revealed elevated paraben metabolites in endometrial and cervical cancer patients compared with controls. Overall, longitudinal studies considering intrinsic and environmental factors are needed in assessing paraben-related cancer risk.